(untitled) (Hoboken, N.J., 2007)
Authored by a panel of experts in the field, this book focuses on hyperspectral image analysis, systems, and applications. With discussion of application-based projects and case studies, this professional reference will bring you up-to-date on this pervasive technology, wether you are working in the military and defense fields, or in remote sensing technology, geoscience, or agriculture.
Keywords: Remote sensing,Multispectral photography,Image processing; Digital techniques